Mapping the current and past distribution of Asian elephants (Elephas maximus) and human-elephant conflict (HEC) in human-occupied landscapes of Peninsular Malaysia. - Tan, Seok Ling (2017)
Conservation planning of Asian elephants (Elephas maximus) requires the understanding of their basic spatial distribution and habitat associations to monitor changes in elephants’ range, which can be used as a proxy for population trends. Elephants in Peninsular Malaysia persist in fragmented landscapes having been extirpated from most of their former geographical ranges due to habitat loss and fragmentation. The current distribution and factors driving distribution patterns of elephants in Peninsular Malaysia are poorly studied and not accurately known. Therefore, this study aims to (1) map the current and past distribution of wild elephants and human-elephant-conflict (HEC) in human-occupied–landscapes of Peninsular Malaysia using a relatively fast and cost-effective approach; (2) understand the temporal changes of elephant and HEC distribution in the past 40 years; and (3) identify what ecological factors influence elephant distribution and habitat use. This study is the first to produce a distribution map of elephants and HEC in Peninsular Malaysia focusing in human-occupied landscapes using systematic semi-structured interview surveys. The study area was the human-occupied-landscapes in Peninsular Malaysia. The structured questionnaires were haphazardly administered to residents via face-to-face interview over a 5x5 km cell grid to gather baseline quantitative information on the distribution of elephants, HEC and temporal changes in both. The survey yielded a total of 5,585 interviews or 2,230 grids encompassing an area of approximately ca. 55,750 km2. Elephants were detected in only 12.9% (289 grids) out of the total grids surveyed. Up to 40 years ago, elephants were still detected in 616 grids, having lost 68% of their detected range. HEC was reported in 68.5% (198 grids) of all the grids with elephant detection and crop damage was the most common form of HEC. The occupancy model showed that the main determinant of elephant’s area of use is proportion of forest cover within 225 km2 indicating elephant’s occurrence and HEC incidences are spatial phenomena and occur on entire landscapes. The human density factor was also an important determinant of elephant’s area of use. Elephants could tolerate areas with low human density but avoid these after a threshold was achieved. Contrastingly, elephants in Peninsular Malaysia do not seem to thrive outside forests and protected areas stressing the need to retain large contiguous forest blocks and protected areas in addition to improving connectivity to facilitate elephants’ movement in human-occupied-landscapes. Additionally, HEC mitigation efforts such as erecting electric fences should be in place for areas with high HEC incidence to reduce impacts and loss caused by HEC. Finally, the use of questionnaire surveys has proven to be a relatively fast and effective way to obtain information about elephant and HEC presence and this study could be repeated after five or ten years to monitor changes in distribution of elephants and HEC.